2019
DOI: 10.1155/2019/2345042
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled, Multicentre Trial of the Effects of a Shrimp Protein Hydrolysate on Blood Pressure

Abstract: In this randomized, double-blind, placebo-controlled, multicentre, parallel, 8-week study, the efficacy of a daily dose of 1200 mg of protein hydrolysate from Coldwater Shrimp (Pandalus borealis) on ambulatory and office blood pressure was investigated in 144 free-living adults with mild to moderate hypertension. The primary outcomes of the study were daytime ambulatory systolic blood pressure and office blood pressure. During the 8-week intervention period and in the intention-to-treat analysis (n=144), there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Concerning the antihypertensive potential of peptides, Musa-Veloso et al [ 60 ] carried out a randomized, double-blind, placebo-controlled, multicenter trial to evaluate whether 1.2 g of shrimp peptides could have an effect on adults with mild to moderate hypertension (n = 144, mean age of 55 years old). Authors indicated a significant reduction of blood pressure, possibly due to a reduction in angiotensin II levels.…”
Section: In Vivo Studies: Description Of Resultsmentioning
confidence: 99%
“…Concerning the antihypertensive potential of peptides, Musa-Veloso et al [ 60 ] carried out a randomized, double-blind, placebo-controlled, multicenter trial to evaluate whether 1.2 g of shrimp peptides could have an effect on adults with mild to moderate hypertension (n = 144, mean age of 55 years old). Authors indicated a significant reduction of blood pressure, possibly due to a reduction in angiotensin II levels.…”
Section: In Vivo Studies: Description Of Resultsmentioning
confidence: 99%
“…Hypertension is an important risk factor that can increase the chance of developing heart attack or stroke. Clinically, systolic blood pressure (SBP) 140 mmHg or above and/or DBP 90 mmHg or above are considered as hypertension [ 79 ]. It is estimated that over a billion people (1 in 5 women and 1 in 4 men) are suffering from hypertension.…”
Section: The Role Of Dietary Bioactive Peptides In Hypertensionmentioning
confidence: 99%
“…Recently, numerous antihypertensive peptides are isolated from different food sources such as milk [ 80 ], casein [ 81 , 82 ], egg white ovotransferrin [ 22 ], rice bran [ 1 ], wheat [ 83 ], soybean [ 84 ], potato [ 85 ], turmeric and ginger [ 9 ], quinoa [ 62 ], black cumin [ 86 ], coix [ 87 ], pistachio [ 88 ], hazelnut [ 89 ], mung bean [ 90 ], lentil [ 91 ], seahorse [ 92 ], egg white from ostrich [ 93 ], chum salmon [ 94 ], skate [ 95 ], cuttlefish [ 96 ], Sipuncula [ 97 ], bighead carp [ 98 ], shrimp ( Pandalus borealis ) [ 79 ], and beef [ 99 ]. The isolated dietary protein-derived peptides have been demonstrated to exhibit antihypertensive activities through influencing various molecular mechanisms including inhibition of angiotensin-converting enzyme (ACE), reduction of SBP, decrease of angiotensin II levels and AT1R expression, enhancing vasodilation, improving central blood pressure and arterial stiffness, and inhibition of vasoconstriction via PPAR- γ expression [ 9 , 79 , 84 , 90 ]. Table 4 shows the molecular mechanisms of antihypertensive peptides isolated from various dietary sources.…”
Section: The Role Of Dietary Bioactive Peptides In Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal research has yielded encouraging findings, indicating that interventions lasting six weeks with the use of hydrolysates demonstrate promise in alleviating insulin resistance [33]. Early indications from clinical trials have indicated that marine hydrolysates can have clinically beneficial metabolic effects [34][35][36].…”
Section: Introductionmentioning
confidence: 99%